Incidencia de la blue light en la aparición del síndrome visual informático en personas de 15 a 30 años de edad Sector las Malvinas, Ventanas - Los Ríos octubre 2018 – abril 2019 - Macías Santana, Karla Briggitte (2019)
The Computer Visual Syndrome (SVI), is a set of symptoms related to mobile devices, come to consultation complaining of fatigue, blurred vision, itchy eyes, headache, eye pain, dry and irritated eye, hypersensitivity to blue light. The proposed objective was to determine the incidence of blue light in the appearance of computer visual syndrome in people aged 15 to 30 years. A quantitative, descriptive and diagnostic study was carried out to evaluate the problem of Visual Computer Syndrome in inhabitants of Las Malvinas, the electronic devices they use every day and their effects on visual health. The universe was of 186 participants with ages of 15 to 30 years. The work showed that the female sex is the predominant in this study being the most outstanding 15 to 20 years, 66% have problems in their vision due to personal pathological background, 41% are students, 63% has never been done a visual checkup, in the visual acuity test, 56% presented a visual acuity without correction from 20/40 to 20/100, Within the symptoms, the predominant ones are blurred vision and headache.